Academic and Mental Health Needs of Students on a Canadian Campus - Robinson, Alexandra M.; Jubenville, Theresa M.; Renny, Katerina; Cairns, Sharon L. (Canadian Journal of Counselling and Psychotherapy, 2016)
The focus of the current study was to examine student-identified academic and mental health concerns, the prevalence of psychological distress in the student population, student utilization of counselling services, and perceived barriers to accessing counselling services. A convenience sample of students (N = 400) from a large university in western Canada completed a four-page questionnaire that included The General Population – Clinical Outcomes in Routine Evaluation (CORE-GP) and researcher-generated questions. Survey results indicated that 63.1% of students identified having academic concerns, 36.1% of students identified anxiety as a concern, and 31.9% endorsed depressive symptomology as a mental health concern. The criteria for clinical psychological distress were met by 42% of males and 43% of females, yet only a small portion of students identified accessing counselling services for these concerns. Students reported numerous barriers that impeded access to counselling services. Recommendations for targeting student-identified concerns and addressing potential barriers to counselling services are offered.